Agronomic Traits Adaptation of Subtropical Soybean from East Asia in Indonesia - Risliawati, Andari; Lestari, Puji; Terryana, Rerenstradika Tizar (AGRIVITA Journal of Agricultural Science, 2026)
Soybean, a protein-source vegetable legume, is one of the major commodities in Indonesia, leading to intensive breeding activity. Around 120 soybean varieties have been released, with an average yield of 1.5–2 tons per hectare and an average in-country production of around 300 thousand tons per year. Introducing subtropical soybeans is an approach to enrich the genetic variance of local soybeans to increase the yields. A total of 112 subtropical soybeans from East Asia were planted in the lowland tropic region, and their agronomic traits adaptation was observed. The area was selected to assess the photoperiod sensitivity of soybean species, which originated from subtropical regions. All genotypes flowered and were able to produce mature pods. Principal Component Analysis (PCA) was used as a prior analysis to gain a better understanding of the dimensionality of datasets. Eight principal components (PC) were produced, with 67.60% of data variation explained by the first three PCs. Biplot analysis identified 30 potential genotypes that exhibited better performance, which were grouped into 4 distinct clusters, and each cluster had its specific identity traits. This preliminary finding could be a basis for further research for reference when selecting genotypes as gene sources in soybean breeding programs.